Effects of Exchange Rate Volatility on Economic Growth: Evidence from West African Monetary Zone (International Journal of Scientific Research and Management (IJSRM), 2021)
Abstract: This study examined the effects of exchange rate volatility on economic growth in four WAMZ countries. The study uses the pooled ordinary least squares, fixed effects and random effects models, and obtains a robust standard error estimate of the model by applying xtreg, cluster()fe. The empirical analysis shows that the effects of exchange rate volatility on economic growth is insignificant. The results also show a positive correlation between exports and economic growth. This implies that policies aimed at increasing exports through an appropriate exchange rate may be beneficial countries. In addition, the analysis also shows a positive and significant link between imports and economic growth rates. Therefore, this confirms that the countries actually benefit from imports resulting from the competitive pressure generated by the import of consumer goods and professional knowledge, and also from the transfer of technology embodied in the import of goods by producers. Hence, the policy of removing import barriers will benefit the countries. In addition, the results show that there is a positive correlation between the nominal exchange rate and economic growth rate. Therefore, it shows that the nominal exchange rate depreciation policy can play an important role in improving the economic growth of the countries. However, the research results show that there is an inverse relationship between the real exchange rate and economic growth. Considering the importance of the real exchange rate, this study suggests the introduction of a common currency in the WAMZ to reduce the negative effects of the real exchange rate on economic growth.